Kritik Sosial Teks ‘Hidup Ini Brengsek Dan Aku Dipaksa Menikmatinya’ Dalam Semiotika Roland Barthes - Alifia Arsya Nabela; Dwi Prasetyo (LPPM Stikosa-AWS, 2022)
Social criticism is a means of communication in conveying an idea to create a social change. The research with the title Social Criticism in the Text